The Annals of Biomedical Engineering on Critical Size Bone Defect: A Review - Ahmad Zainol Had, A.; Azmi, L.; Abdullah, A. R. (Universiti Sains Islam Malaysia, 2024)
Bone can heal on its own through the process known as bone remodelling. Nonetheless, a critical size bone defect will hinder the natural bone-healing process and may not allow for complete fracture healing. These requires surgical intervention by employing the use of bone tissue implants and in need of realignment and fixation for proper fracture healing. Traditional knowledge of bone injury and fracture healing must be comprehended thoroughly for a proper invention of bioengineered material or devices that could enhance the physiological process. Heretofore, engineered materials used to address critical size bone defects have encountered various challenges and improvement be it in bone grafting or choices of mechanical stabilization devices. To date, researchers have been mainly focussing on the alternative material for bone graft substitute albeit the selection of fixators to establish mechanical stabilization are as important. This review highlighted the challenges, improvement and advancement in mechanical stabilization devices and bone graft substitute with respect to the physiological process of bone fracture healing. Identifying these challenges would help assist the researcher in an expedition toward the recovery and restoration of critical size bone defects.